Comportamiento del consumidor turístico durante el proceso de compra. Caso de estudio: Mercado Nacional de Artesanías de San Salvador - Retana de Guirola, Yeyli Yalitza; Pérez Hernández, Mónica Esther (Empresa y Sociedad, 2024)
El Salvador has managed to position itself in the tourism market as a competitive destination at a national and international level, promoting domestic and inbound tourism as a key to generating foreign exchange and jobs. Handicrafts not only represent cultural manifestations with historical roots but also a source of income for thousands of families that depend on this informal sector. Indeed, craft traditions are one of the best examples of the connection between art and industry. The main artisanal receptacle in which these cultural pieces are exhibited in El Salvador is the National Handicraft Market of San Salvador, since artisan products from all the country’s departments are presented, making it an attraction rich in folklore for national and international tourists, which has become a relevant economic engine, thus attracting the attention of state authorities. For this reason, it becomes important to analyze the behavior of the tourist consumer in the decision-making process to purchase artisanal products, and the identification of the economic, demographic and psychographic factors that influence said behavior during the tourist consumer’s purchase process, with the In order to maintain the validity of the artisan sector, which represents an important form of production, source of employment, support for the local economy and an opportunity to promote national identity and culture.